The Role of Environmental Narratives in English Language: The Impact of Using Environmental Stories on Students’ Consciousness - Mehwish Zulfiqar; Dr. Ali Ahmad; Basma Abtool (Dialogue Social Science Review (DSSR), 2025)
The study examines the effect of environmental stories on enhancing students’ English proficiency and ecological awareness within their school setting (Sterling, 2001; Orr, 2004). Specifically, the research examines the role of environmental stories in teaching, focusing on their impact on students’ reading and writing abilities, as well as their understanding of ecological themes. Grounded in ecocriticism, sociocultural theory, constructivist learning, and transactional reading theory, the research employed a pre-test/post-test experimental design involving 50 students divided into control and experimental groups. Over six weeks, the experimental group engaged with environmental narratives addressing climate change, deforestation, and pollution, while the control group followed a standard curriculum. Data were gathered using reading comprehension tasks and vocabulary quizzes and analyzed with paired sample t-tests using SPSS. Results from SPSS analysis revealed a statistically significant improvement in the experimental group’s reading comprehension, vocabulary, and environmental understanding (p = 0.000). These findings suggest that integrating environmental narratives into English Language Teaching not only strengthens linguistic skills but also deepens students’ ecological consciousness, contributing to broader educational goals aligned with sustainable development. The findings of this study align with previous research that recognizes the dual value of incorporating environmental topics into ELT. As Stibbe (2015) and Frawley (2014) note, this research demonstrates that ecological narratives can enhance both language skills and environmental awareness. This research aligns with the findings of Stibbe (2015) demonstrating that ecological narratives benefit children in both language learning and understanding of nature. The significant improvement in the experimental group's ecological knowledge and language proficiency further supports the claim that the inclusion of environmental content can deepen students’ understanding of ecological issues while enhancing their language competencies, as Ghosn (2013) found in his study.